2012
DOI: 10.1113/jphysiol.2012.227397
|View full text |Cite
|
Sign up to set email alerts
|

The motor cortex drives the muscles during walking in human subjects

Abstract: Key points• It is often assumed that automatic movements such as walking require little conscious attention and it has therefore been argued that these movements require little cortical control.• In humans, however, the gait function is often heavily impaired or completely lost following cortical lesions such as stroke.• In this study we investigated synchrony between cortical signals recorded with electroencephalography (EEG) and electromyographic signals (EMG activity) recorded from the tibialis anterior mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
307
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(357 citation statements)
references
References 43 publications
33
307
1
1
Order By: Relevance
“…59 As noted in a recent systematic review, however, the clinical usefulness of these approaches for prediction of outcomes and forecasting responsiveness to training has yet to be established. 149 To justify the greater time and resource requirements needed to acquire these state-of-the-art measurements, in order to have true value as biomarkers for recovery, they will need to provide a more accurate picture of future walking status than do prediction rules based on clinical measures.…”
Section: Variables Associated With Walking Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…59 As noted in a recent systematic review, however, the clinical usefulness of these approaches for prediction of outcomes and forecasting responsiveness to training has yet to be established. 149 To justify the greater time and resource requirements needed to acquire these state-of-the-art measurements, in order to have true value as biomarkers for recovery, they will need to provide a more accurate picture of future walking status than do prediction rules based on clinical measures.…”
Section: Variables Associated With Walking Functionmentioning
confidence: 99%
“…59 The role of the motor cortex in human walking has been elucidated by studies in humans showing that: (1) subthreshold transcranial magnetic stimulation (TMS) to activate inhibitory interneurons in the motor cortex suppresses the locomotor EMG in the ankle dorsi -and plantar flexor muscles, 61 (2) suprathreshold TMS activates dorsiflexors to the same extent as during volitional contractions in sitting, 62 and (3) electroencephalographic (EEG)-EMG coherence shows synchrony in the frequency domain between the primary motor cortex and the dorsiflexors during walking. 59 Most of the evidence related to corticomotor control of walking in humans has focused on the dorsiflexor muscles, in which there is step-to-step modulation of muscle activity during level overground walking (or at least a constant drive to facilitate spinal circuitry). 59,61 The role of the motor cortex in other locomotor muscles remains to be elucidated, as does a potentially modified role of supraspinal inputs following injury wherein walking speeds are slower and the task of walking requires more cognitive attention.…”
Section: Supraspinal Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies did not show a clear effect of walking speed on EMG-EMG (Hansen et al, 2005;den Otter et al, 2004) or EEG-EMG (Petersen et al, 2012) coherence. In accordance with these studies we also observed no influence of walking speed on the coherence variables.…”
Section: Variablesmentioning
confidence: 99%